Crop Diversification as a Determinant of Household Decision-Making in the Production of Roselle Plant in Mwea Sub-County, Kenya - Kyalo, Justin (International Journal of Social S ciences and Information Technology, 2018)
This study sought to analyze crop diversification as a determinant of household decision making towards production of the Roselle plant. The study employed a stratified sampling technique which involves dividing your population into homogenous subgroups and then taking a simple random sample in each group.The target population was 200 farmers drawn from four areas i.e. Karie, Kangai, Ngariama and Mutithi.A sample size of133 respondents who consisted of employees working in the Roselle farms was selected. A confidence level of 95% which yields a margin of error of 5% which is 0.05 was used to arrive at the sample size. This study revealed that a majority of the respondents grow a variety of crops apart from Roselle. Crop diversification has a great effect on farmers’ incomes since a high number of respondents indicated that diversification on crops grown increases the incomes generated through farming.The study concluded that crop diversification had an effect on decisions of farmers to grow Roselle plant from the study due to combating the challenge of seasonality, increase of income streams and also it helps to deal with pests and diseases.
Keywords: Crop diversification; Roselle plant